Polytene chromosomes arrangement of chironomus and polypedilum midge larvae - Salleh , S.; Ahmad , A.K. (Pusat Sistematik Serangga ,UKM, 2013)
Chironornus and Polypedilum are among important genera in Chironomidae family. Both genera are abundance and very diverse in aquatic ecosystem. Chironomus and Polypedilum are dominant and frequently found during the sampling processes. The objectives of this study were to establish the standard polytene chromosome arrangement of Chironomus and Polypedilum and to distinguish variable polytene chromosome arrangement of both genera. This study was based on cytogenetic approach which revealed the species-specific characteristics in each polytene chromosome arms. The results also showed that polytene chromosomes of Chironomus and Polypedilum have some similarities and differences in polytene chromosome arms. Both genera have four polytene chromosomes which comprise of three long combined arms and one short ann. There were also several distinct forms of polytene chromosome observed from both genera. The Nuclear Organizing Region (NOR) structure was found in chromosome I of Chironornus while BR structure was found in chromosome I of Polypedilum. There is a rearrangement pattern found in chromosome II and two BR structures in chromosome IV of Chironomus while two large puffing forms found in chromosome III and BR structure, rearrangement pattern and NOR found in chromosome IV of Polypedilum. Cytotaxonomic study revealed the cryptic structure of polytene chromosomes arrangement has provided important source of indentificating the genus or spesies name. This study indicates that chromosome arrangement could aid in revealing Chironomus and Polypedilum diversity.